Implementation of Financial Accounting System at The Regional Finance and Asset Management Agency of Banten Province - Fatimah Pembayun (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to examine the implementation of Financial Accounting System at the Banten Province Financial Management Agency. This research method is a descriptive quantitative research method. The data used in this study include primary data and secondary data. The implementation of Financial Accounting System at the Banten Province Financial Management and Asset Agency has been carried out in accordance with the applicable regulations.